Caesalpinbondin A, a Novel Diterpenoid Lactone With an Unprecedented Carbon Skeleton from the Seeds of Caesalpinia bonduc - Fei, Dong-Qing; Li, Hui-Hong; Chen, Xiao-Han; Cui, Wen-Bo; Zhang, Zong-Ping; Zhan, Xiao-Qing; Wang, Mei-Jie; Qi, Feng-Ming; Zhang, Zhan-Xin; Li, Er-Wei (Frontiers in Chemistry, 2022)
One novel diterpenoid lactone named caesalpinbondin A (1) that possesses an unprecedented tetracyclic ring system in which a 6/6/5-fused tricyclic ring and a 4,5-dimethyldihydrofuran-2(3H)-one was connected by a C-C single bond comprising a 5-(naphtho[2,3-b]furan-7-yl)dihydrofuran-2(3H)-one moiety was isolated from the seeds of Caesalpinia bonduc. Its chemical structure was established by extensive spectroscopic methods, and its absolute configuration was further determined by single-crystal X-ray diffraction analysis and electronic circular dichroism (ECD) calculation. Biological evaluation suggested that compound 1 demonstrated potent anti-Alzheimer’s disease (AD) bioactivity, which could delay paralysis of transgenic AD Caenorhabditis elegans. A possible biogenetic pathway of 1 was also proposed.